Expanded ring NHC silver carboxylate complexes as efficient and reusable catalysts for the carboxylative cyclization of unsubstituted propargylic derivatives - Cervantes Reyes, Alejandro; Saxl, Tobias; Stein, Philipp; Rudolph, Matthias; Rominger, Frank; Asiri, Abdullah Mohamed; Hashmi, A. Stephen K. (ChemSusChem, 2021)
Stabilized by a bulky N-heterocyclic carbene [BPDPr, 1,3-bis(2,6-diisopropylphenyl)-1,3-diazonine-2-ylidene] ligand, new silver carboxylate complexes of the form BPDPrAgO2C-R (R=Me, Ph) have been synthesized and fully characterized in solution and in the solid state and implemented as sole catalysts (base-, additive-, and, in some cases, solvent-free) in the challenging fixation of carbon dioxide to unsubstituted propargylic derivatives for the synthesis of oxazolidinones and α-methylene cyclic carbonates. Derived from X-ray diffraction studies, the molecular geometry and the concept of buried volume were employed to describe the structural and steric features of these silver complexes. Their stability and efficiency as catalysts have been demonstrated by the synthesis of 29 carboxylation products (72-98 % yield) at low catalyst loadings (0.01-1.5 mol%). Characteristics are high turnover numbers (up to 9400), catalyst recyclability (up to 96 % yield after the 7th cycle with no decomposition of the silver complex), and the possibility to scale-up the reaction.